O cordel em sala de aula: contribuição ao ensino de língua portuguesa - Spadafora, Sheila Aparecida de Moraes Ibiapino (2010)
The theme of this paper is cordel literature in the classroom. This theme was chosen based on the need of recapturing this element of Brazilian folk culture in school life, thereby fulfilling the dual objective of students becoming both acquainted to and also fostering aspects which are part of their own historical heritage. Moreover, it focuses also on the objective of being an aid in the study of the Portuguese Language, more specifically as far as reading and writing are concerned. Our approach is dual and stems from a technical and practical focus as applied to Text Linguistics which in the seventies sought to analyze texts beyond the level of words and sentences to arrive at genres, based on the work of Bakhtin and other researchers. Based on its social character and thereby until recently shunned and viewed as being a lesser educational subject matter the theme is now conversely prestigious and well considered. Accordingly, we begin by drawing on the broad background of cordel literature as a whole and follow-up by considering the content of the most recent Brazilian Ministry Of Education s publications focusing on Brazilian Educational orientation guidelines, the so-called National Curricular Parameter Publications. As an application basis for the theoretical approach adopted, a project involving fifth-year elementary school students in a prestigious school in the city of Sao Paulo was developed. The end result of this project was the edition of a collection of thirty-nine Odyssey Epic retextualization texts in Cordel. By means of this end product, we aimed at demonstrating that well stimulated students even if within the initial phases of their education are very able to produce coherent, cohesive and creative texts, aligned to the genres being studied by them